Pyrazolo[4,3-e][1,2,4]triazolo[1,5-c]pyrimidines and Structurally Simplified Analogs. Chemistry and SAR Profile as Adenosine Receptor Antagonists - Redenti, Sara; Ciancetta, Antonella; Pastorin, Giorgia; Cacciari, Barbara; Moro, Stefano; Spalluto, Giampiero; Federico, Stephanie (Current Topics in Medicinal Chemistry, 2016)
Adenosine was defined as a neuromodulator which exerts its action by interaction with specific G-protein coupled receptor termed adenosine receptors. Adenosine receptors are expressed in several tissues and cells of our body and exist as four different subtypes of these receptors: A1, A2A, A2B and A3. In the last years significant efforts were made to obtain highly potent and selective ligands for the four adenosine receptors subtypes. Both agonists and antagonists were used as pharmacological tools to study therapeutic implications of enhancing or blocking the adenosine receptors activity, and some of these compounds have reached clinical phases. The pyrazolo[4,3-e][1,2,4]triazolo[1,5-c]pyrimidines (PTPs) represent one of the several templates designed as adenosine receptor antagonists. A lot of synthetic work was made on this scaffold in order to obtain potent A2A and A3 antagonists. Here were reviewed the synthetic approaches followed by both academia and industry to introduce different substituents at different positions of the PTP nucleus, in particular at the 2, 5, 7, 8 and 9 positions. Nevertheless PTP derivatives are tricyclic compounds with a high molecular weight which exhibit limitations such as poor aqueous solubility and difficult synthetic preparation. With the aim to obtain derivatives with the same potency and selectivity of PTP but with better drug-like properties, researchers made structural simplification of this scaffold. Replacement of the pyrazole or triazole rings of PTP led to the [1,2,4]triazolo[1,5-c]pyrimidine and pyrazolo[3,4- d]pyrimidine derivatives, respectively. Synthetic strategies for these compounds were reported, combined with the SAR profile on the adenosine receptors.
Keywords: 2